2019
DOI: 10.17576/jsm-2019-4803-20
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Equal Channel Angular Pressing Processing Routes on Corrosion Resistance and Hardness of Heat Treated A356 Alloy

Abstract: Equal channel angular pressing (ECAP) via routes A and Bc was used to process heat treated A356 alloy. The samples produced a range of microstructures in order to investigate the effect of straining on its corrosion behavior in 3.5 wt. % NaCl solution and hardness. The ECAP was conducted at room temperature in a mold with channel angle of 120°. The results show that brittle coarse silicon particles were effectively fragmented into smaller size in the Al-rich matrix after the processing. The hardness and corros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…They also reported that route C had more stable Tafel polarization curves than routes A and Bc, and they attributed this to the high fraction of HAGBs and grain boundary misorientations present. Gebril et al [ 74 ] reported that amongst the routes they tested, route Bc was the most effective in improving the corrosion resistance of the A356 Alloy. They attributed that to the higher refinement of the structure produced by route Bc compared to route A.…”
Section: Resultsmentioning
confidence: 99%
“…They also reported that route C had more stable Tafel polarization curves than routes A and Bc, and they attributed this to the high fraction of HAGBs and grain boundary misorientations present. Gebril et al [ 74 ] reported that amongst the routes they tested, route Bc was the most effective in improving the corrosion resistance of the A356 Alloy. They attributed that to the higher refinement of the structure produced by route Bc compared to route A.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the brittle and hard eutectic Si particles might break during deformation, and with further deformation their mean free space could be further reduced. Since strength of materials is inversely related to the free space of particles, the hardness of the samples increases with increasing the pass number (Gebril et al 2019;Haghshenas et al 2009aHaghshenas et al , 2009b. Thus, the application of high strain results in increased hardness of the A356 alloy due to increased fragmentation of the eutectic Si particles and reduced grain size in addition to the increase in density of dislocation.…”
Section: Hardness Of A356 After Ecapmentioning
confidence: 99%